Pollen morphology, ultrasculpture and ultrastructure of Poiretia Vent. (Leguminosae–Papilionoideae–Dalbergieae–Adesmia informal clade) - Antonio-Domingues, Higor; Perez, Ana Paula Fortuna [UNESP]; Rossi, Mônica Lanzoni; Martinelli, Adriana Pinheiro; da Luz, Cynthia Fernandes Pinto (Taylor & Francis, 2022)
Pollen morphology, ultrasculpture and ultrastructure were investigated for Poiretia in search of morphological characters of taxonomic importance using light microscopy as well as scanning and transmission electron microscopy. Additionally, principal components analysis was done to elucidate patterns of variation among the species. Pollen grains are small to medium size, isopolar, prolate spheroidal to prolate, 3-zonocolporate, colporus with operculum, membrane and margo are ornamented. Five pollen types are recognised and described based on mesocolpium exine ultrasculpture. Exine consists of a compact tectum, eutectate, tectate perforate to semitectate, the infratectum is collumelar and granular, foot layer discontinuous to absent in aperture region and endexine is continuous. A comprehensive description of the operculum, membrane ornamentations and the ultrastructure of exine were given for all species in the genus, nine of which were not previously analysed palynologically. Systematic implications of the palynological variations found in the literature and through light, scanning and transmission electron microscopical analyses were discussed. This article describes the importance of the characterisation of Poiretia pollen grains, which contributes to the systematics of the Adesmia informal clade. The class of endoaperture, ultrasculpture of mesocolpium and apocolpium, and ultrastructure of tectum, foot layer, and endexine support the eurypalynous status of Poiretia and are useful to recognise some species that have problematic delimitation (P. latifolia, P. coriifolia, P. unifoliolata, P. mattogrossensis, P. elegans, P. marginata) as well as groups of species.
Keywords: Dalbergioid; Fabaceae; palynology; palynotaxonomy; plant systematics